Perbandingan Kadar Garam Natrium dan Kalium pada Tes Ferning Lendir Mulut - Mardiati, Siti Muflichatun (JURNAL SAINS DAN MATEMATIKA, 2007)
ABSTRACT---The objective of this study was to know natrium and potassium levels of oral mucus ferning test. The object were 30 women, that were taken their oral mucus once within the 6th to 19th day of menstruation. The ferning test of oral mucus were examined with light microscope. The data distribution was analized by Kolmogorf – Smirnov, followed by non – parametric statistics. The mean, median and standard deviation were calculated with descriptive analysis. The Wilcoxon signed rank test was used to analyze the differentiation between the natrium and potassium levels of oral mucus in groups. The result of this study shows that the oral mucus potassium level is higher than natrium level. It means that potassium more important than natrium in the oral mucus ferning test. Keywords : potassium, natrium, ferning score, oral mucus